Apuntes sobre algunos elementos del contenido del derecho al debido proceso colectivo en el Perú - Glave Mavila, Carlos (2017)
Given the lack of regulation about the protection of collective rights in Peru, the main goal of this investigation is to show what should be some elements of the content of a due collective process. Thus each of its elements is studied taking into account the Peruvian jurisprudence and legislation.